Flood mitigation management practice: a comparison between stormwater management road tunnel (SMART) and sponge city methods - Ahmad, Arfah Juneena; Ayob, Mohd Fairullazi (Faculty of Built Environment, Universiti Malaya, 2023)
Flash flood in Malaysia urban is no longer a surprise incident as it has become a widespread natural disaster that frequently happened every year. The geographical of Malaysia with equatorial climate experiences consistently high temperatures with high relative humidity and influenced by the northeast and southwest monsoons have provided heavy rainfall during the monsoon season. Although the flood issue has been given an important focus under the disaster management implementation in Malaysia, there is critical demand to improve the present flood mitigation management practice to overcome unforeseen flood disaster issues over the long term. The annual occurrence of floods in Malaysia has caused a very big impacts to the lives of humans and other living beings that requires serious attention and better “solution alternative” measures in urban areas. Commentators have remarked that the current urban flood management method, i.e., Stormwater Management and Road Tunnel (SMART) has not been proven as the long-term best solution to overcome the unforeseen flood disaster issues over the long term. There have been suggestions from the scholars to explore and adopt a new method, i.e., Sponge City concept that is still scarce in Malaysia but has been substantially adopted in China to overcome the urban flood issues. Therefore, this paper is prepared to present the outcome of the study on the comparison between the present Stormwater Management and Road Tunnel (SMART) and the newly concept of Sponge City with specific reference to the urban flood mitigation management in Malaysia. This study employs a quantitative research strategy to collect primary data from fifty-eight (58) respondents that approximately represents 73% of the entire distributed questionnaires or a total of 80 potential respondents that was identified to meet the specified criteria, with the objective to get their opinions on the comparison between the two competing methods, i.e., the present SMART tunnel, and the newly Sponge City concept for urban flood mitigation management in Malaysia. The findings revealed that the majority of the respondents chose Sponge City because it is greater advantages than the SMART tunnel method to overcome the issues of flood disaster in the urban areas. Although the Sponge City concept could be deemed appropriate for consideration as the new and better flood mitigation management method in Malaysia, it demands a holistic assessment to view the relevancy of Sponge City implementation and its investment over the life span for achieving economic sustainability and Sustainable Development Goals (SDGs).